Indicators of Sharia-Compliant Hotels as a Strategy for Advancing Halal Tourism in Blitar Raya - Farih Fahmi, Moh; Hanif Fajrin, Ahmad; Syaifuddin, Rahmad; Mutafarida, Binti (El-kahfi | Jurnal Ekonomi Islam, 2025)
Indonesia seeks to establish itself as a leading global destination for inclusive tourism based on Islamic values, one of which is the provision of sharia-compliant hotels, particularly in the Blitar Raya region. Such accommodations have significant potential to attract Muslim travelers who seek comfort and peace aligned with sharia principles. While Muslim-friendly tourism ensures basic amenities—such as prayer spaces and halal food—sharia hotels provide a more comprehensive implementation of Islamic values across all aspects of service and management. This study investigates the urgency of developing sharia-compliant hotels in Blitar Raya as a strategic driver for advancing Muslim-friendly tourism. It also aims to formulate a set of feasibility indicators that align with Islamic principles. Using a qualitative research design, this study adopts a phenomenological approach grounded in the framework of maqāṣid al-sharīʿah to assess both the necessity and criteria for Muslim-friendly hotel development. Findings reveal that while the demand for sharia-compliant hotels in the region is growing, there is no standardized framework to guide their implementation. Therefore, measurable and practical indicators are essential for evaluating hotel readiness and promoting consistent standards. These indicators include physical elements (e.g., halal food, worship facilities) and non-physical factors (e.g., Islamic service ethics, management style, and environment). The study contributes by proposing ten weighted indicators for assessing the suitability of hotels in Blitar Raya for Muslim tourists. This framework serves to enhance service quality, support tourism development, and strengthen Indonesia’s role as a global Muslim-friendly tourism.